Corporate Social Responsibility (CSR) during Covid-19 Pandemic: The Implementation from Unicorn Companies - Kurniawan Aji Prabowo (Research Synergy Foundation, 2021)
The COVID-19 pandemic has become a global problem. COVID-19 affects how companies handle employees, customers, and, therefore, the community. Unicorn companies have an essential role in overcoming the pandemic, and they are partnered with the Indonesian government to assist the government in fighting Covid-19. Unicorn companies use the CSR program in helping the community to face the pandemic and the new normal era. This paper aims to explain the response of Indonesian unicorn companies in handling the pandemic through CSR and explain why CSR is useful and necessary in facing the new normal era. The approach was taken in this paper was to survey the literature such as previous studies, annual reports, and news reports on the CSR program from Indonesian unicorn companies during the Covid-19 pandemic, especially CSR for vital stakeholders such as employees, customers, communities, and societies. Employees, consumers, and communities are the foremost significantly suffering from Covid-19. Indonesia's unicorn companies specialize in CSR in several sectors like basic needs, healthcare support, and education. CSR in the community is carried out by Tokopedia with the Nakamate program, while Go-Jek carries out CSR for consumers by providing in-app telemedicine. Besides that, Gojek also assists its driver-partners with financial assistance. On the other hand, other unicorns such as Traveloka, OVO, Bukalapak carry out CSR by donating money, medical equipment, and basic needs to communities affected by the pandemic. This study only adopted a descriptive qualitative research design; consequently, the data obtained were somewhat limited. Further, research can use the interview method with stakeholders to get a more in-depth review. To the best of the author's knowledge, this paper is one of the few studies to propose research on the CSR of unicorn companies in Indonesia during the COVID-19 pandemic, obtained from qualitative data collected during the pandemic.